Calculating TIN-Based 3D Sight Distance and Its Evaluation on Drivers Free-Flow Speed. (4th August 2021) - Sahaf, Ali; Abdoli, Ali; Mohamadzadeh Moghaddam, Abolfazl
Abstract : Sight distance during driving may be limited by side factors such as mountain slopes or trees and buildings in horizontal curves and by the dome of the arc in vertical curves, and the night vision also can be limited in the sag vertical curves by the vehicle's light. Analyzing driver's sight distance in the road is very important for traffic safety. In this regard, in order to help the designer, the current rules and guidelines propose the two-dimensional analysis model for the sight distance. In this analysis, the sight distance is calculated separately in the combination of horizontal and vertical curves, and the smallest amount is considered as the sight distance. While, after constructing and operating the road, drivers control their vehicle according to the conditions in their 3D space. Nowadays, given the remarkable advances in computer science, there are many possibilities for 3D modeling of the route. In this research, the goal is to calculate the three-dimensional stopping sight distance at each spatial point by computer modeling the existing roads. The speed of various drivers with conventional riding vehicles under free traffic conditions was obtained by a GPS device. The results showed that, in places such as curves, given the provision of sufficient stopping sight distance, driver's free-flow speed reduces. Thus, another factor affecting the speed of the drivers is the curvature change rate. Finally, using nonlinear regression modeling a logical relationship was determined and extracted between the three factors of driver's free-flow speed, 3D stopping sight distance, and curvature change rate of the path.